Assessing the Impact of Covid-19 Pandemic On Public Secondary School Students Education in Ekiti State (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study assessed the Impact of Covid-19 Pandemic on Public Secondary School Students’ Education in Ekiti State.The study adopted a descriptive research design of the survey type. The population was 11,245 students of Ekiti State Public Secondary Schools. A total of 120 students was purposively selected from 3 public secondary schools. A questionnaire titled Impact of Covid-19 on Education of Secondary School Students was used for the study. The instrument was subjected to face and content validity. The reliability of the instrument was ascertained using test re-test method. Copies of the instrument were administered on 20 respondents who were not among sample for the study on two occasions with an interval of two weeks. The reliability coefficient of 0.81 was obtained which was high enough for the study. Data collected were tested descriptively. The result showed that the extent of impact of Covid-19 on educational system of students in Ekiti-State was moderate. The finding also revealed that the level of student’s education during Covid -19 in Ekiti State was high. The study therefore recommended that teachers should be encouraged to utilize social media network for teaching so as to avoid students’ idleness. Students should be more intimated with the use of social network for learning at available opportunity.